Future Foods - Mikkola, Heimo (IntechOpen, 2017)
It is anticipated that by 2050 we will have nine billion people to feed-how can we manage? As scarcities of agricultural land, water, forest, fishery and biodiversity resources, as well as nutrients and nonrenewable energy are foreseen, insect rearing is one solution for food and feed security in the future. In this book, we have nine chapters ranging from mushroom, insect, and earthworm farming to smart packaging and 3D printing of future foods. However, because of their biological composition, several issues should be considered, such as microbial safety, toxicity, palatability, and the presence of inorganic compounds. Specific health implications ought to be kept in mind especially if mushrooms, earthworms, or insects are reared on waste products. Allergies induced through insects' ingestion also deserve attention. A possible HACCP plan has been described considering pre-requirements in insect production and transformation.